2017
DOI: 10.1101/199927
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Many rare genetic variants have unrecognized large-effect disruptions to exon recognition

Abstract: Any individual’s genome contains ∼4-5 million genetic variants that differ from reference, and understanding how these variants give rise to trait diversity and disease susceptibility is a central goal of human genetics1. A vast majority (96-99%) of an individual’s variants are common, though at a population level the overwhelming majority of variants are rare2–5. Because of their scarcity in an individual’s genome, rare variants that play important roles in complex traits are likely to have large functional e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 86 publications
0
9
0
Order By: Relevance
“…We next compared the performance of PEPSI and PEPSI‐noSS in classifying SDVs among SNPs assayed in the MFASS experiment (Cheung et al, ) using several state‐of‐the‐art tools, including HAL (Rosenberg et al, ), SPANR (Xiong et al, ), and MutPredSplice (Mort et al, ). We first compared the sensitivity and precision of PEPSI and PEPSI‐noSS to SPANR in classifying SDVs from all 2,094 SNPs in the curated test set given that SPANR is capable of scoring both exonic and intronic SNPs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We next compared the performance of PEPSI and PEPSI‐noSS in classifying SDVs among SNPs assayed in the MFASS experiment (Cheung et al, ) using several state‐of‐the‐art tools, including HAL (Rosenberg et al, ), SPANR (Xiong et al, ), and MutPredSplice (Mort et al, ). We first compared the sensitivity and precision of PEPSI and PEPSI‐noSS to SPANR in classifying SDVs from all 2,094 SNPs in the curated test set given that SPANR is capable of scoring both exonic and intronic SNPs.…”
Section: Resultsmentioning
confidence: 99%
“…To carry out this benchmark analysis, we used splicing functional assay data from the Multiplexed Functional Assay of Splicing using Sort‐seq (MFASS) experiment (Cheung et al, ). The MFASS experiment assayed a total of 27,733 ExAC SNPs within or adjacent to 2,339 exons.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We compared MMSplice with three stateof-the-art splicing variant scoring models: SPANR [17], HAL [18] and MaxEntScan [7] on the held-out Vex-seq test data. The methods HAL [18] and SPANR [17] have been reported to be the two best performed existing methods on a recent large-scale perturbation assay probing 27,733 rare variants [29], while Max-EntScan [7] was considered as a baseline reference model. SPANR scores exonic and intronic SNVs up to 300 nt around splice junctions.…”
Section: Mmsplice Improves the Prediction Of Variant Effect On Exon Smentioning
confidence: 99%
“…To further compare models on predicting exon skipping level with independent datasets that no model has been trained on, we used the splicing functional assay from Cheung et al [29]. Cheung et al found 1,050 splicedisrupting variants (SDVs), the majority are extremely rare, after examining 27,733 ExAC single-nucleotide variants (SNV) with Multiplexed Functional Assay of Splicing using Sort-seq (MFASS) ( Fig.…”
Section: Mmsplice Classifies Rare Splice Disrupting Variants With Higmentioning
confidence: 99%